Proposed Improvement to Contract Management in Supply Department - Margusano, Ardi Andra; Hermawan, Pri (Jurnal Aplikasi Manajemen, 2015)
Coal mining industries currently are in unfavorable condition, therefore the Companyshall reduce the cost and/or increase efficiency in order to equalize the decrease of coalprice. Reducing the cost can be done by 2 methods either reducing the usage i.e. quantity byefficiency or reducing price which is usually done by negotiation as the main strategy of thecompany. Beside negotiation, appropriate contract management will deliver a good contributioneither directly or indirectly towards cost reduction. Symptom indicates a requirement ofimprovement to contract management. The solutions are efficient management, increasingstaffs'ability, increasing staffs'motivation, improvement of policy and procedure, developmentof simple spreadsheet, implementation of optimum cost strategy, owner estimation review,and holding regular socialization. Value added delivered by these solutions includesstaffs productivity, higher saving, better contract quality, higher bargaining position, minimizingloss of production day, and avoidance of additional cost.